2019
DOI: 10.1371/journal.pone.0214966
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on machine learning based algorithms for prediction of motorcycle crash severity

Abstract: Motorcycle crash severity is under-researched in Ghana. Thus, the probable risk factors and association between these factors and motorcycle crash severity outcomes is not known. Traditional statistical models have intrinsic assumptions and pre-defined correlations that, if flouted, can generate inaccurate results. In this study, machine learning based algorithms were employed to predict and classify motorcycle crash severity. Machine learning based techniques are non-parametric models without the presumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 71 publications
(107 reference statements)
2
40
0
1
Order By: Relevance
“…In addition to the abovementioned categorizations, the algorithms can be further divided into either parametric or nonparametric groups. 25 The set of parameters in a parametric algorithm is fixed which confines the function to a known form. In nonparametric methods, the algorithm does not make any assumptions about the function to which it will map its variables.…”
Section: Supervised Machine Learning Algorithms: (Common Algorithms Amentioning
confidence: 99%
“…In addition to the abovementioned categorizations, the algorithms can be further divided into either parametric or nonparametric groups. 25 The set of parameters in a parametric algorithm is fixed which confines the function to a known form. In nonparametric methods, the algorithm does not make any assumptions about the function to which it will map its variables.…”
Section: Supervised Machine Learning Algorithms: (Common Algorithms Amentioning
confidence: 99%
“…In 2019, Machine Learning (ML) algorithms for the prediction and classification of motorcycle crash severity were employed in a research by Wahab, L., and Jiang, H. [46]. Machine-learning-based techniques are non-parametric models without any presumption of the relationships between endogenous and exogenous variables.…”
Section: Related Workmentioning
confidence: 99%
“…The study revealed that ML techniques outperform statistical techniques in terms of accuracy and efficiency. Location type, collision type, day and week of the crash, road surface condition, and shoulder condition were some of the factors that determined the motorcycle crash severity [24]. Decision trees (J48, ID3, and CART) and naïve Bayes algorithms were employed using the WEKA software tool for predicting crash severity.…”
Section: Literature Reviewmentioning
confidence: 99%